Vishnu as Keshava - 016 - Saurabh Saxena (2022)
Image courtesy : Saurabh Saxena - https://puratattva.in/ In the Keshava form Vishnu holds Shankha in his top right hand, Chakra in the top left, Gada in the bottom left, and Padma in the bottom right. A chart of various forms of Vishnu based on how each hand holds his signature objects can be found here. https://shodhganga.inflibnet.ac.in/bitstream/10603/153280/10/08_chapter%203.pdf